Children caught between two ethnic sides. Challenges for community social reconstruction - Ajduković, Dean (2005)
After strive in multiethnic communities people not only suffer from posttraumatic stress but equally important from multiple losses – family members, home, relatives, friends, job, professional identity, sense o community. Communities as the people knew before the war are fragmented, social networks and other normal support mechanisms are shattered In multiethnic societies, the previously irrelevant differences between “ ingroup” and “ outgroups” can become of paramount importance (Ignatieff, 1999). It makes people insist on previously irrelevant characteristics as a support for building own new social identity (group an individual) – language, history, culture, looks, dressing, food. The children who live in such communities adapt to circumstances and follow the adult behavior models. However, conditions should be created for children to develop individual capacities and become aware of their own value as an individuals, not only through group identity. For a child growing up in ethnically divided communities who is denied right of choice of multiple group belonging, any single identity becomes imposed and does not serve the best interest of the child.